Nanostructured Hydrogels - Montoro, Sérgio Roberto [UNESP]; Medeiros, Simone de Fátima; Alves, Gizelda Maria (Elsevier, 2013)
Polymer systems can be developed into a variety of functional forms to meet industrial and scientific applications. In general, they are presented in four common physical forms: (1) linear free chains in solution, (2) covalently or physically cross-linked reversible gels, (3) micro and nanoparticles, and (4) chains adsorbed or in surface-grafted form. Hydrogels are polymeric particles consisting of water-soluble polymer chains, chemically or physically connected using, in general, a cross-linking agent. These materials do not dissolve in water but may swell considerably in aqueous medium, demonstrating an extraordinary ability (>20%) to absorb water into the reticulated structure. Such features make these materials promising tools in the biomedical field, especially as controlled drug release systems. This chapter describes recent progress in the development and applications of polymeric nanostructured hydrogels, mainly in the context of biomedical devices. Additionally, it reports the significant advances in synthesis and characterization strategies of these materials. Special attention is devoted to smart or stimuli-responsive bionanogels, which mimic the property of living systems responding to environmental changes such as pH, temperature, light, pressure, electric field, chemicals, or ionic strength, or a combination of different stimuli. Consequently, these bionanogels offer an efficient solution to various biomedical limitations in the field of drug administration. © 2014 Elsevier Inc. All rights reserved.
Keywords: Biomedical; Bionanogels; Cross-linking agents; Hydrogels; Nanostructured hydrogels; Polymer colloids; Polymer systems; Polymeric gels